UNSUR MAJAS LOKALITAS DALAM KUMPULAN PUISI LELAKI DAN TANGKAI SAPU KARYA IYUT FITRA - Wahyudi, Fitra; Hasanuddin WS, Hasanuddin WS (Universitas Negeri Padang, 2019)
The research was conducted aimed at analyzing the utilization of the locality of figure of speeches in a collection of poems entitled Lelaki and Tangkai Sapu written by Iyut Fitra. In addition, with the existence of this research, it can be seen the purpose of the poet using the locality assembly in his collection of poems, namely as a form of satire and introducing locality in his culture. In this study, used a type of qualitative research with descriptive methods. The majors of locality used by the poet in this collection of poems are as many as ten majas, namely (1) the comparison of metaphors of locality, (2) comparison of simile locality, (3) comparison of personification of locality, (4) comparison of metonymy locality, (5 ) the comparison of the antonomasia of locality, (6) the insinuation of the irony of locality, (7) the insinuation of locality allegory, (8) the insinuation of locality parables, (9) the insinuation of locality cynicism, and (10) majas satire locality. The locality institution that is most used by poets is Majas satire of irony.Keywords: locality, Iyut Fitra, figure of speech, poems